Proteomic analysis of Plasmodium falciparum histone deacetylase 1 complex proteins - Engel, Jessica; Przyborski, Jude M. (Experimental parasitology, 2019)
Plasmodium falciparum histone deacetylases (PfHDACs) are an important class of epigenetic regulators that alter protein lysine acetylation, contributing to regulation of gene expression and normal parasite growth and development. PfHDACs are therefore under investigation as drug targets for malaria. Despite this, our understanding of the biological roles of these enzymes is only just beginning to emerge. In higher eukaryotes, HDACs function as part of multi-protein complexes and act on both histone and non-histone substrates. Here, we present a proteomics analysis of PfHDAC1 immunoprecipitates, identifying 26 putative P. falciparum complex proteins in trophozoite-stage asexual intraerythrocytic parasites. The co-migration of two of these (P. falciparum heat shock proteins 70-1 and 90) with PfHDAC1 was validated using Blue Native PAGE combined with Western blot. These data provide a snapshot of possible PfHDAC1 interactions and a starting point for future studies focused on elucidating the broader function of PfHDACs in Plasmodium parasites.